Two new species of Leptoceridae (Trichoptera) from Florida, USA - Rasmussen, Andrew K.; Harris, Steven C.; Denson, Dana R. (Zootaxa, 2008)
Diagnoses, descriptions, and illustrations of male and female genitalia are given for two new species of Leptoceridae: Setodes chipolanus n. sp. from limestone-bottom streams within the Chipola River Basin and Ceraclea limnetes n. sp. from small natural lakes lying within the Munson Sandhills of the Apalachicola National Forest.